Morphology and properties of foamed high crystallinity PEEK prepared by high temperature thermally induced phase separation. Issue 1 (26th July 2021) - Rusakov, Dmitrii; Menner, Angelika; Spieckermann, Florian; Wilhelm, Harald; Bismarck, Alexander
Abstract: Polyetheretherketone (PEEK) is a high‐performance semi‐crystalline thermoplastic polymer with outstanding mechanical properties, high thermal stability, resistance to most common solvents, and good biocompatibility. A high temperature thermally induced phase separation technique was used to produce PEEK foams with controlled foam density from PEEK in 4‐phenylphenol (4PPH) solutions. Physical and mechanical properties, foam and bulk density, surface area, and pore morphology of foamed PEEK were characterized and the role of PEEK concentration and cooling rate was investigated. Porous PEEK with densities ranging from 110 to 360 kg/m 3 with elastic moduli and crush strength ranging from 13 to 125 MPa and 0.8 to 7 MPa, respectively, was produced. Abstract : Temperature induced phase separation of PEEK from 4‐phenylphenol solutions allows for production of high porosity PEEK foams with excellent mechanical properties.